Toroidal, compression and vortical dipole strengths in 124Sn - Kvasil, J.; Repko, A.; Nesterenko, V. O.; Kleinig, W.; Reinhard, Paul-Gerhard; Lo Iudice, N. (Physica Scripta, 2013)
The toroidal, compression and vortical dipole strength functions in semi-magic 124Sn (and partly in doubly magic 100,132Sn) are analyzed within the random-phase-approximation method with the SkT6, SkI3, SLy6, SV-bas and SkM* Skyrme forces. The isoscalar (T = 0), isovector (T = 1) and electromagnetic ('elm') channels are considered. Both convection j c and magnetization jm nuclear currents are taken into account. The calculations basically confirm the previous results obtained for 208Pb with the force SLy6. In particular, it is shown that the vortical and toroidal strengths are dominated by jc in the T = 0 channel and by jm in the T = 1 and 'elm' channels. The compression strength is always determined by jc. It is also shown that the 'elm' strength (relevant for the (e,e′) reaction) is very similar to the T = 1 one. The toroidal mode resides in the region of the pygmy resonance. So, perhaps, this region embraces both irrotational (pygmy) and vortical (toroidal) flows. © 2013 The Royal Swedish Academy of Sciences.
CRIS-Team Scopus Importer:2023-07-24